2013
DOI: 10.5433/1679-0359.2013v34n3p995
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e qualidade do milho doce em diferentes populações de plantas

Abstract: ResumoO objetivo do presente estudo foi avaliar o efeito da população de plantas sobre os componentes de produção e a composição química de grãos de dois híbridos de milho doce no cultivo de "InvernoPrimavera". O delineamento experimental utilizado foi o de blocos completos casualizados com quatro repetições. Os tratamentos constituíram-se da combinação entre híbridos de milho doce (Tropical Plus e RB-6324) e populações de plantas (40.000, 55.000, 70.000, 85.000 e 100.000 plantas ha -1 ), no esquema fatorial 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
1
3
0
4
Order By: Relevance
“…There was good control of the conditions applied to the present study due to the low experimental variation coefficients herein observed. EY recorded the highest VCe, fact that was already expected due to the polygenic nature of such trait; this result was corroborated by other studies (Oliveira Jr. et al 2006;Souza et al 2013;Oliboni et al 2013).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There was good control of the conditions applied to the present study due to the low experimental variation coefficients herein observed. EY recorded the highest VCe, fact that was already expected due to the polygenic nature of such trait; this result was corroborated by other studies (Oliveira Jr. et al 2006;Souza et al 2013;Oliboni et al 2013).…”
Section: Discussionsupporting
confidence: 87%
“…The mean EY estimate was higher than that found by Souza et al (2013), Oliboni et al (2013), and Oliveira Jr. et al (2006). This information is very important because it allows highlighting the potential of the tested genotypes and makes it possible using them in the final tests of the breeding program in question.…”
Section: Discussionmentioning
confidence: 70%
“…Valor superior de CV% para produtividade de espigas comerciais (PEC) foi observado por Souza et al (2013), avaliando os componentes da produção e a composição de grãos de híbridos de milho-doce, com valor de 18%.…”
Section: Resultsunclassified
“…Expressive sugar accumulation in the kernels is blocked by the sugar conversion into starch in the endosperm, specifically in the super sweet genotype group (sh2) (Tracy 2010). The small presence of the ADP-glucose pyrophosphorylase enzyme in the endosperm catalyzes the reaction between glycose-1-phosphate and adenosine triphosphate and drastically reduces the starch synthesis (Tracy 2001;Souza et al 2013). The PROT in the sweet corn kernels was described (p < 0.05) by the quadratic model for the inoculant main factor (Fig.…”
Section: Sourcementioning
confidence: 99%